What determines adherence to treatment in cardiovascular disease prevention? Protocol for a mixed methods preference study. Issue 2 (27th October 2011) - Jan, Stephen; Usherwood, Tim; Brien, Jo Anne; Peiris, David; Rose, John; Hayman, Noel; Howard, Kirsten; Redfern, Julie; Laba, Tracey; Cass, Alan; Patel, Anushka
Abstract : Background: Significant gaps exist between guidelines-recommended therapies for cardiovascular disease prevention and current practice. Fixed-dose combination pills ('polypills') potentially improve adherence to therapy. This study is a preference study undertaken in conjunction with a clinical trial of a polypill and seeks to examine the underlying reasons for variations in treatment adherence to recommended therapy. Methods/design: A preference study comprising: (1) Discrete Choice Experiment for patients; and (2) qualitative study of patients and providers. Both components will be conducted on participants in the trial. A joint model combining the observed adherence in the clinical trial (revealed preference) and the Discrete Choice Experiment data (stated preference) will be estimated. Estimates will be made of the marginal effect (importance) of each attribute on overall choice, the extent to which respondents are prepared to trade-off one attribute for another and predicted values of the level of adherence given a fixed set of attributes, and contextual and socio-demographic characteristics. For the qualitative study, a thematic analysis will be used as a means of exploring in depth the preferences and ultimately provide important narratives on the experiences and perspectives of individuals with regard to adherence behaviour. Ethics and dissemination: Primary ethics approval was received from Sydney South West Area Health Service Human Research Ethics Committee (Royal Prince Alfred Hospital zone). In addition to usual scientific forums, the findings will be reported back to the communities involved in the studies through site-specific reports and oral presentations.